2000
DOI: 10.1007/s00585-001-1584-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional electric field measurements in the ionospheric footprint of a flux transfer event

Abstract: Abstract. Line-of-sight Doppler velocities from the SuperDARN CUTLASS HF radar pair have been combined to produce the ®rst two-dimensional vector measurements of the convection pattern throughout the ionospheric footprint of a¯ux transfer event (a pulsed ionospheric¯ow, or PIF). Very stable and moderate interplanetary magnetic ®eld conditions, along with a preceding prolonged period of northward interplanetary magnetic ®eld, allow a detailed study of the spatial and the temporal evolution of the ionospheric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 25 publications
5
23
0
Order By: Relevance
“…signatures which, although generated by FTE activity, persist beyond the interval of active reconnection. Observations presented by McWilliams et al (2001) suggested that only for the first part of its lifetime in the radar field-of-view, did an HF transient map the footprint of an active reconnection region, moving mainly longitudinally under the magnetic tension force induced by the IMF B Y component and with a phase velocity roughly twice the convection speed. After this, the transient slowed to the convection velocity, moving antisunward with the reconnected field lines.…”
Section: Cutlass Hf Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…signatures which, although generated by FTE activity, persist beyond the interval of active reconnection. Observations presented by McWilliams et al (2001) suggested that only for the first part of its lifetime in the radar field-of-view, did an HF transient map the footprint of an active reconnection region, moving mainly longitudinally under the magnetic tension force induced by the IMF B Y component and with a phase velocity roughly twice the convection speed. After this, the transient slowed to the convection velocity, moving antisunward with the reconnected field lines.…”
Section: Cutlass Hf Observationsmentioning
confidence: 99%
“…After this, the transient slowed to the convection velocity, moving antisunward with the reconnected field lines. It should be stated that the study of McWilliams et al (2001) was exceptional in that twodimensional vector observations of the convection pattern were available throughout the ionospheric footprint of an FTE. The authors noticed a reduction in the spectral width of the feature as it propagated, as is also evident in the present observations.…”
Section: Cutlass Hf Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hosokawa et al (2002) carried out a statistical analysis of the HF radar spectral width and reported that the spectral width is small above 80 • magnetic latitude. McWilliams et al (2001a) investigated poleward moving pulsed ionospheric flows (PIFs) in the HF radar data and pointed out that the spectral widths are relatively high at the equatorward edge of the PIFs, but decrease with increasing latitude. Milan et al (2002) analyzed HF radar polar patches and clearly showed that the spectral width within the patch becomes considerably narrow as it moves poleward.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between PIFs, FCEs and FTEs is discussed more thoroughly in Wild et al (2001). A detailed discussion of the mapping of FTEs to the ionosphere in PIFs appears in McWilliams et al (2001).…”
Section: Effects Of Solar Wind Variationsmentioning
confidence: 99%